Open Public Information in Finance Operational Management PT Kereta Api Indonesia - Abid Setiawan; Arifiani Widjayanti; Nurliah Nurdin (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this research is to analyze why information disclosure in the financial operational management of PT Kereta Api Indonesia has not been optimal, and to develop strategies in the framework of public information disclosure in the operational management of PT Kereta Api Indonesia. In this research the author chose to use a qualitative descriptive method. The results showed that the fundamental problem faced by public bodies lies in their inability to determine the types of information that can be categorized as public information and which information is exempt. The presence of the Law on Public Information Disclosure is important, especially to encourage public participation, which is an important element of the creation of good governance. Public participation is very important in encouraging the smooth running of public activities, the presence of the Public Information Disclosure Act is a driving force for the development of the principles of transparency and public accountability in every implementation of its duties and functions. Administrative order and work culture will increase, so that the potential for KKN practices will be eradicated. It is the duty of every public body to make it easier for the public to access public information. The accuracy of determining which information is public and which information is exempt and which public information must be provided at any time, periodically and at any time is the key to success for public bodies to implement effective Public Information Disclosure. This success in general has been made in a regulation as a legal basis for every public body to implement Public Information Disclosure, the presence of Information Management and Documentation Officers as coordinator of public information management and services, provides a lot of convenience for the community to obtain public information. The next cohesion is characterized by the diversification of the use of communication media, including online media, which can be used as an interaction between information requesters and public bodies.